2017
DOI: 10.1016/j.ijhydene.2017.05.150
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of different carbon fuels on a hybrid direct carbon fuel cell

Abstract: Recently hybrid direct carbon fuel cells (HDCFC) has attracted great attention, combining the advantages of solid oxide fuel cells and molten carbonate fuel cells, to convert energy of carbon to electricity directly without chemical combustion. In this work, three processed carbon fuels including activated carbon, carbon black and graphite have been employed to investigate influence of the chemical and physical properties of carbon on the HDCFC performance in different anode atmospheres at 650-800 °C. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…To investigate the effects of liquid Sn anode on the HDCFC performance, the I-V and I-P curves of four Ni-YSZ anode supported cells with different Sn contents (0, 10, 20 and 50 wt%) were measured at 750 °C, as shown in Figure 1. For Sn-free anode, the peak power density exhibited about 65 mW cm -2 , which is much smaller than previously reported by the anode supported cells of carbon black pore former due to insufficient gas pathways in anode structure (11). When introducing Sn phase into anode, the OCV (open circuit voltage) doesn't change significantly, indicating the OCV is still dominated by the co-effects of carbon and carbonates other than liquid Sn phase.…”
Section: Resultsmentioning
confidence: 63%
“…To investigate the effects of liquid Sn anode on the HDCFC performance, the I-V and I-P curves of four Ni-YSZ anode supported cells with different Sn contents (0, 10, 20 and 50 wt%) were measured at 750 °C, as shown in Figure 1. For Sn-free anode, the peak power density exhibited about 65 mW cm -2 , which is much smaller than previously reported by the anode supported cells of carbon black pore former due to insufficient gas pathways in anode structure (11). When introducing Sn phase into anode, the OCV (open circuit voltage) doesn't change significantly, indicating the OCV is still dominated by the co-effects of carbon and carbonates other than liquid Sn phase.…”
Section: Resultsmentioning
confidence: 63%
“…However, the volatile matter decomposes as a loss, and only part of the decomposition takes part in the chemical reactions before the cell is on the operation (cell's target temperature is 750 °C in here). There are 30 wt% loss from BC tested in nitrogen, while only a little loss from GC shown in TG results in our previous paper [27].…”
Section: Compositionmentioning
confidence: 53%
“…We have demonstrated the carbon oxidation process in a hybrid direct carbon fuel cell using carbon black as fuel in our previous research [26]. Our initial investigation on the application of different carbon fuels in HDCFCs showed that GC in an anode-supported cell exhibited poor cell performance of 75 mW cm -2 , which is much lower than 100 and 210 mW cm -2 at 750 C with carbon black and activated carbon as the fuel, respectively [27]. Among all the fuels, biomass carbon (BC, pyrolysed medium density fibreboard) generated the best cell performance with a maximum power density of 878 mW cm -2 at 750 C [28].…”
Section: Introductionmentioning
confidence: 99%
“…When the cell was ramping to the operating temperature (750 °C), the flow rate was exchanged into 20 ml min -1 . The current density-voltage(I-V) curves were tested by an IM6 Electrochemical Workstation (ZAHNER, Germany) with four-probe configuration, described as previous work [8].…”
Section: Cell Fabrication and Performance Testmentioning
confidence: 99%
“…The molten carbonate and solid oxide electrolyte based DCFC prototypes have been extensively studied [5,6]. A recent design is the hybrid direct carbon fuel cell (HDCFC), which is a composite of a solid oxide fuel cell and molten carbonate fuel cell which gives higher power density by extending active reaction sites and limiting the cathode corrosion [7,8].…”
Section: Introductionmentioning
confidence: 99%